경기 일부지역 중학생의 야식 섭취실태 - 조유진(Yu-Jin Cho); 김미현(Mi-Hyun Kim); 김명희(Myung-Hee Kim); 최미경(Mi-Kyeong Choi) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
The purpose of this study was to investigate the night eating habits of middle schoolers. A total of 705 middle school students residing in Gyeonggi were surveyed about their dietary habits related to night eating. Among the total subjects, 59.9% (n=422) had night eating more than once a week and were classified into a night eating group (NEG). The main reason for night eating was hunger (79.1% of NEG) and the highest proportion of night eating was related to food purchased by family (39.3% of NEG). Most of the NEG had night eating in their home with family members, and the time with highest frequency of night eating was between 10 p.m. and 11 p.m.. About 33% of the NEG went to bed within an hour after night eating and 69.2% of the NEG did not report any change after night eating. The most common factors considered when choosing a night eating menu, in order of frequency, were taste, hygiene, and amount. The favorite items on the night eating menu were frozen desserts, fresh fruits, chicken, fruit juice, Ramen, pizza, and Jajangmyeon. The most frequent menu choices were fresh fruits, frozen desserts, Ramen, chicken, yogurt, and fruit juice. The NEG had higher scores for picky eating (P<0.01), overeating (P<0.01), salty eating (P<0.01), and irregular meal times (P<0.001) compared to the non-NEG. Consequently, the NEG had more dietary problems than the non-NEG and their night eating behaviors were related to family habits. Night eating was mainly dominated by a diet of carbohydrates and fats, and the intake frequency and preference for foods with low nutritional value were high; thus, a practical and systematical nutrition education is required. Seasonal and comparative studies on night eating status according to various times and amounts of night eating are also required. 본 연구에서는 경기 일부지역에 거주하는 중학생 705명을 대상으로 야식 섭취형태, 야식 선택 시 고려사항, 야식 메뉴별 기호도 및 섭취빈도, 야식 섭취에 따른 식습관을 비교분석함으로써 청소년의 야식 섭취상태와 그에 따른 문제점을 제시하고자 하였다. 주 1회 이상 야식을 한다는 대상자를 '야식군'으로 분류하였고, 전체대상자 중 야식군은 422명(59.9%)이었다. 야식을 먹는 주된 이유는 배가 고파서(79.1%)로 나타났으며, 야식을 먹게 되는 경로는 가족이 구입해서가 39.3%로 가장 높았고, 야식을 먹는 장소는 집이 96.2%로 높은 비율을 보였다. 야식을 먹는 시간은 밤 10~11시가 40.3%로 가장 높았으며, 야식 대상자의 32.9%가 야식 후 1시간 이내에 잠자리에 들고, 야식을 먹고 난 후 다음날 아침의 변화에 대하여 69.2%가 변화가 없다고 답하였다. 야식 메뉴를 선택할 때 맛, 위생, 양 등의 순서로 중요하게 고려하는 것으로 나타났다. 기호도가 높은 야식 메뉴는 빙과류, 과일류, 치킨, 과일주스, 라면, 피자, 자장면 순이었으며, 섭취빈도가 높은 것은 과일류, 빙과류, 라면, 치킨, 요구르트, 과일주스 순이었다. 야식군은 비야식군보다 편식(P<0.01), 과식(P<0.01), 짜게 먹기(P<0.01), 불규칙한 식사시간(P<0.001)의 점수가 높아 식습관이 좋지 않은 것으로 나타났다. 이상의 결과를 종합할 때, 조사대상 중학생의 약 60%가 주 1회 이상 야식을 섭취하고 있었으며, 늦은 저녁 시간에 배고픔으로 인하여 가족과 함께 야식을 섭취하는 경우가 많고, 야식 메뉴에 있어서도 탄수화물 및 지방이 주를 이루며 영양밀도가 낮은 메뉴들에서 기호도 및 섭취빈도가 높았다. 또한 야식군이 비야식군에 비해 식습관도 바람직하지 않은 것으로 나타났다. 본 연구는 비교적 많은 청소년을 대상으로 이들의 올바른 야식 지도에 활용할 수 있는 유의미한 결과를 도출하였지만, 야식에 대한 정의가 다소 불분명하고 여름 한 철에 조사되어 야식 메뉴가 한정적으로 제시된 제한점을 가지고 있다. 따라서 앞으로 보다 다양한 야식시간과 양 그리고 계절에 따른 야식 섭취상태를 비교 분석하는 연구가 이루어져야 할 것이다.